2018
DOI: 10.1111/jfb.13752
|View full text |Cite
|
Sign up to set email alerts
|

Introgressive hybridization between wild and domestic individuals and its relationship with parasitism in brook charrSalvelinus fontinalis

Abstract: The effects of introgression on parasitism in brook charr Salvelinus fontinalis were investigated in 28 lakes with various levels of stocking in Québec, Canada. No effect of genetic background on parasitism was found at the individual level. Body length seemed to explain most of the variation observed at this level, with largest fish being more infected. However, lakes with the greater average domestic genetic background were found to display significantly lower parasite prevalence and diversity. Since our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…The main driver of morphological variation was the lake identity, suggesting that shape of individuals was primarily determined by the characteristics of the population they belonged to. Local environmental differences among lakes, which vary in terms of abiotic (e.g., temperature, dissolved oxygen levels, depth, lake area; Marie et al 2012, Létourneau et al 2018) and biotic conditions (e.g., presence of competitors, parasitic fauna; Gossieaux et al 2018), have been shown to influence morphology (Magnan 1988, Bertrand et al 2008, Baillie et al 2016, Zastavniouk et al 2017). Brook Trout were previously shown to display highly variable morphologies among geographically close lakes (Kazyak et al 2015) and are known to be phenotypically plastic (Kazyak et al 2015, Samways et al 2015, Zastavniouk et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main driver of morphological variation was the lake identity, suggesting that shape of individuals was primarily determined by the characteristics of the population they belonged to. Local environmental differences among lakes, which vary in terms of abiotic (e.g., temperature, dissolved oxygen levels, depth, lake area; Marie et al 2012, Létourneau et al 2018) and biotic conditions (e.g., presence of competitors, parasitic fauna; Gossieaux et al 2018), have been shown to influence morphology (Magnan 1988, Bertrand et al 2008, Baillie et al 2016, Zastavniouk et al 2017). Brook Trout were previously shown to display highly variable morphologies among geographically close lakes (Kazyak et al 2015) and are known to be phenotypically plastic (Kazyak et al 2015, Samways et al 2015, Zastavniouk et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted sampling over two time periods (2007–2008 and 2014–2016) in three wildlife reserves (Portneuf 47°10′7.8″ N, 72°20'32.7″ W, Mastigouche 46°42'45.2″ N, 73°25'37.7″ W, and Saint‐Maurice 47°04′00.0″ N, 73°08′28.5″ W) in Québec, Canada (see Gossieaux et al 2018). Stocking practices are rigorously controlled in these reserves, and stocking history of lakes has been documented since 1964 (provided by the ministère des Forêts, de la Faune et des Parcs, Québec, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations